Characterization of antimicrobial, antioxidant, anticancer property and chemical composition of michelia champaca seed and flower extracts - Lee Seong Wei; Wendy Wee; Julius Young Fu Siong; Desy Fitrya Syamsumir (2011)
This study was carried out to characterize antimicrobial, antioxidant and anticancer activities of Michelia champaca seed and flower extracts. The main objective of the present study was to reveal the medicinal values of M. champaca seed and flower for human uses. Antimicrobial property of M. champaca seed and flower extracts were revealed by using two fold microdilution method whereas antioxidant activity of the extract was determined with DPPH radical scavenging method. The anticancer property of the plant extract was revealed through Colorimetric MTT (tetrazolium) assay. The minimum inhibitory concentration values of M. champaca seed and flower extracts ranged from 15.6 to 125mg/l and 7.8 to 62.5mg/l, respectively in which both of the plant extracts were found can inhibit the growth of all the tested bacterial isolates namely A. hydrophila, E. tarda, E. coli, Flavobacterium sp., Klebsiella sp., P. aeruginosa, Salmonella sp., V. alginolyticus, V. cholerae and V. parahaemolyticus. M. champaca flower extract was able to control the growth of E. tarda, E. coli, Flavobacterium sp., P. aeruginosa and V. cholerae at the concentration of 7.8mg/l whereas A. hydrophila, Klebsiella sp. and V. alginolyticus were failed to grow at the concentration 15.6mg/l. The M. champaca flower extract was also able to control the growth of Salmonella sp. and V. parahaemolyticus at the concentration of 62.5mg/l. At the maximum concentration of M. champaca seed and flower extracts were found can inhibit only 40% of DPPH whereas the IC50 value of M. champaca seed and flower extract against MCF-7 cells was 1.98 ±0.31μg/ml and 1.86 ± 0.21μg/ml, respectively. A total of 9 chemical compounds were successfully identified in M. champaca’s flower extract whereas 37 chemical compounds were found in the leaf extract. The findings of the present study indicated that medicinal values of M. champaca seed & flower extracts in terms of antimicrobial and anticancer are promising.